2021
DOI: 10.1186/s13023-021-01954-7
|View full text |Cite
|
Sign up to set email alerts
|

A questionnaire-based study to comprehensively assess the status quo of rare disease patients and care-givers in China

Abstract: Background There are over 16.8 million rare disease patients in China, representing a large community that should not be neglected. While the public lack the awareness of their existence and difficult status quo, for one reason that they exist as a rare and special group in our society, for another reason that all sectors of the community haven’t introduced and propagandized them suitably. However, as a special group with more difficulties in all aspects than normal healthy persons, they need e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…It often leads to extra clinical tests and unnecessary treatments which were costly and time-consuming that further decreased the motivation of patients towards prophylaxis treatment and ultimately increased complications. These nding was consistent with those of published studies[28, 35,36].…”
Section: Discussionsupporting
confidence: 94%
“…It often leads to extra clinical tests and unnecessary treatments which were costly and time-consuming that further decreased the motivation of patients towards prophylaxis treatment and ultimately increased complications. These nding was consistent with those of published studies[28, 35,36].…”
Section: Discussionsupporting
confidence: 94%
“…Notably, the results that caregivers had significantly severe depression symptom and anxiety than patients seemed surprising but were consistent with a published study on other chronic disease [ 38 ]. Apart from the small sample of patients, these results can be partially explained by the fact that the majority of family caregivers were parents, who were extremely concerned about the physical conditions of their children and had to bear tremendous burden (such as difficulty in social life, significant time cost and financial burden) [ 39 ], suggesting the great needs of caregivers for mental interventions such as aid of psychological counseling and support from other caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…This was in line with previous studies reported that many caregivers with OI children had family relationships deteriorated or received no social support [ 4 , 8 ], highlighting the necessity to help families of RBD cope with these problems effectively and increase their adjustment to the disease. In this regard, attending patient groups or care centers, which have been confirmed to be one of the most effective ways [ 39 ], is highly recommended for RBD families to obtain social support by sharing information of the disease, difficult conditions experienced, and ways to cope with these availably.…”
Section: Discussionmentioning
confidence: 99%
“…The low number of patients with disability certificates is not only an issue for RD patients but people with disabilities in general, which may be associated with the bureaucracy of the process [ 116 ], stigma, and discrimination [ 117 ]. Not surprisingly, 69.6% of RD patients relied on the income of family members [ 118 ]. Similarly, RD patients in India often report absenteeism from work/school due to their diseases, leading to higher rates of school dropouts and unemployment when compared to the general population [ 54 ].…”
Section: Current Situation and Key Challenges Related To Rdsmentioning
confidence: 99%